Возможность идентификации параметров асинхронных двигателей энергетическим методом при синусоидальном питании - Ромашихин, Юрий Владимирович; Ромашихина, Жанна Ивановна; Руденко, Никита Андреевич (НТУ "ХПИ", 2017)
В статье проанализированы методы определения параметров асинхронных двигателей и сформулированы основные недостатки существующих методов. Показано, что в качестве исходного метода может использоваться энергетический метод при питании от источника синусоидального напряжения. В статье показано, что получение необходимого гармонического состава обеспечивается за счет разложения синусоидальных сигналов напряжения и тока на интервале, отличном от сетевого. Использование указанных сигналов позволило выполнить определение электромагнитных параметров асинхронных двигателей с погрешностью, которая не превышает 8%.

Purpose. Determination of the electromagnetic parameters of induction motors is due to the need to calculate the losses in steel and copper, the overload capacity of the engine, as well as the construction of performance characteristics. Development of a method for determining the electromagnetic parameters of asynchronous motors with the use of the energy method when feeding from a sinusoidal voltage source. Methodology. In work to determine the electromagnetic parameters, it is proposed to use the energy method, which is based on the balance of the instantaneous power components for each of the elements of the motor replacement circuit. For the development of the energy method, the article considers the possibility of determining the electromagnetic parameters when feeding from a sinusoidal voltage source. Moreover, to obtain the necessary harmonic composition of the voltage and current signals, it is suggested to use pseudo-polyharmonic signals. Results. Features and basic methods of formation of pseudo-polyharmonic signals of voltage and current are considered, the main disadvantages and advantages of the received signals are shown. The decomposition of signals obtained by changing the analysis by limiting the period to the left or to the right, the symmetric and symmetric restriction of the period and the symmetric reflection of the ha lf-period into trigonometric Fourier series, showed the possibility of obtaining the necessary harmoniccomposition of the voltage and current signals. The use of these signals made it possible to determine the electromagnetic parameters of induction motors with sufficient accuracy. Practical value. An analysis of the results obtained showed that the error in determining the electromagnetic parameters by the energy method using pseudo-polyharmonic signals does not exceed 8%.
The possibility of the parameters identification of engine motors by the energy method with sinusoidal feeding
Keywords: мгновенная мощность; метод энергетического баланса; схема замещения; ПП-сигналы; гармонический спектр; induction motor; energy method; instantaneous power